Problems and prospects of small fruit market in Ukraine - Skryhun, Natalya; Kapinus, Larisa (My University, 2013)
An important role in providing population with fruits and vegetables belongs to small fruit crops. Food properties and economic efficiency of to small fruit crops are different, but all of them are essential for the balanced nutrition. Важливу роль у забезпеченні населення з фруктами і овочами належить ягідних культур. Харчові властивості та економічну ефективність для ягідних культур різні, але всі вони мають важливе значення для збалансованого харчування.
Keywords: market of small fruit crops; production; consumption; foodstuffs; ринок ягід; виробництво; споживання; продукти харчування; кафедра маркетингу